Quantum current dissipation in superconducting strings and vortons - Yoshihiko Abe; Yu Hamada; Kota Saji; Koichi Yoshioka (Journal of High Energy Physics, 2023)
Abstract In this work, the current stability is discussed for cosmic strings with the bosonic superconductivity. A non-vanishing curvature of string generally induce the quantum instability of the current-carrying particle. Its decay rates are explored for various types of model parameters, curved string shapes, and decay processes. As a cosmological application, the stability is examined for superconducting strings in the string network and also for cosmic vortons by evaluating their cosmological evolution. The zero mode and hence the vorton cannot be stable in various cases, e.g., with a hierarchy between the current-carrying particle mass off the string and the string tension or with sizable couplings of the current-carrying particle to light species such as the Standard Model particles.